Contesting Fake News - Daniel Rehsmann; Béatrice Roussillon; Paul Schweinzer (Center for Economic Studies and ifo Institute (CESifo), 2023)
We model competition on a credence market governed by an imperfect label, signaling high quality, as a rank-order tournament between firms. In this market interaction, asymmetric firms jointly and competitively control the underlying quality ranking's precision by releasing individual information. While the labels and the information they are based on can be seen as a public good guiding the consumers' purchasing decisions, individual firms have incentives to strategically amplify or counteract the competitors' information emission, thereby manipulating the label's (or ranking's) discriminatory power. Elements of the introduced theory are applicable to several (credence-good) industries which employ labels or rankings, including academic departments, books, music, and investment opportunities.
Keywords: C70; d700; H40; M30; 330; labelling; credence goods; contests; product differentiation